PENERAPAN VISUAL BASIC NET 2010 DALAM SISTEM INFORMASI PEMBAYARAN SPP MAHASISWA - Muhawa sang putri, Muhawa; M.VERDIANSYAH; ATHIFA, RAYZA; ELEGANINO, DZIKRI; MARSANDA (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi Bisnis Riau, 2025)
This study aims to develop a desktop-based student tuition fee payment information system using Visual Basic .NET 2010, with the goal of improving the efficiency of payment data management, reducing tuition arrears, and providing convenience for students in making payments. The system development method used is the waterfall method, which includes stages of requirements analysis, system design, coding, testing, and implementation. The developed system is equipped with features such as student data input, online tuition payment, payment report generation, and payment notifications via email. System testing was conducted by involving several users to gather feedback and evaluation. The results show that the developed tuition payment information system functions well and meets user needs. This system is able to improve payment data management efficiency by 93.61% and also reduce tuition arrears. However, there are still some issues that need improvement, such as integration with the academic information system and the development of mobile payment features.